2006
DOI: 10.4103/0971-9261.25929
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies in the management of jejunoileal and colonic atresia

Abstract: ABSTRACT ABSTRACT ABSTRACTBackground/Purpose: The purpose of this prospective study was to review the operative findings, treatment strategies, as well as the results of management of 46 consecutive cases of jejunoileal and colonic atresia, managed over a 2-year period. Materials and Methods: There were 42 patients with jejunoileal atresia (JIA) and 4 with colonic atresia (CA). The 4 group types were: type I-membranous (n=20), type II-blind ends separated by a fibrous cord (n=6), type IIIa-blind ends with a V-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…Full oral feeding was achieved by 7 th day post-operative in 95% of the children, which is comparable to previous studies, although in one report, [13] full oral intake was achieved as late as 16 th day post-operative. Previous studies have shown that blood loss during the surgery was the only factor contributing to failure of early post-operative oral feeding.…”
Section: Discussionsupporting
confidence: 88%
“…Full oral feeding was achieved by 7 th day post-operative in 95% of the children, which is comparable to previous studies, although in one report, [13] full oral intake was achieved as late as 16 th day post-operative. Previous studies have shown that blood loss during the surgery was the only factor contributing to failure of early post-operative oral feeding.…”
Section: Discussionsupporting
confidence: 88%
“…Two of them developed complications because of unrecognized distal hypoganglionosis. Chadha et al [18] mentioned that prognosis was good in three of the four patients surviving resection and primary anastomosis for right-sided colonic atresia. Two patients had postoperative complications: one had an anastomotic leak and one had a dysfunction, which were successfully treated by other operations.…”
Section: Discussionmentioning
confidence: 99%
“…This has been achieved because of refinements in neonatal intensive care, operative technique, use of total parenteral nutrition (TPN), antenatal diagnosis and neonatal anesthesia [5]. However, survival rates in developing countries are still lower (58.3-71.5%) [4][5][6][7][8]. In two reports from India, survival rate of 82% and 80% has been reported in series of 46 patients of jejuno-ileal atresia (JIA) and colonic atresia (CA), and 15 patients of duodenal atresia (DA), respectively [9,10].…”
Section: Introductionmentioning
confidence: 99%